Patenting Activity on Functional Foods: A Brazilian Scenario - Hilachuk,Daniele (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2021)
Abstract The segment of functional foods is a global trend with expressive growth in recent years. Investments in innovation play an essential role in maintaining the competitiveness of food companies in an increasingly fierce market. This study provides an overview of innovation over the years 2008 to 2020 in the functional foods segment in Brazil by using patenting activity as an indicator of innovation. A patent search was conducted in the National Institute of Intellectual Property (INPI) database to identify patent application records on the following functional foods: (i) gluten-free (ii) lactose-free/low-lactose (iii) probiotic (iv) prebiotic and, (v) enriched/fortified products. The main IPC codes retrieved refer to class A23L (33%), A61K (17%), and A23C (10%), confirming the deposits' relationship with human nutrition. From 2015 on, resident applicants stood out, especially in 2017, with the highest number of deposits in the period. Most patent applications target probiotics (35.3%), followed by fortified/enriched products (25.3%), gluten-free (14.3%), lactose-free/low-lactose (13.3%), and prebiotics (11.8%). Brazilian higher education institutions (HEIs) figure among the top resident patent applicants. University-industry partnerships and research-oriented collaborative networks appear to be a feasible way to foster innovation in the food industry in the country. In summary, the patenting activity of functional foods in Brazil has awakened in recent years, showing trends and opportunities for innovation in the functional food segment.